2022
DOI: 10.1186/s12870-022-03429-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic stimulation-elicited transcriptional responses and biosynthesis of acylated triterpenoids precursors in the medicinal plant Helicteres angustifolia

Abstract: Background Helicteres angustifolia has long been used in Chinese traditional medicine. It has multiple pharmacological benefits, including anti-inflammatory, anti-viral and anti-tumor effects. Its main active chemicals include betulinic acid, oleanolic acid, helicteric acid, helicterilic acid, and other triterpenoid saponins. It is worth noting that some acylated triterpenoids, such as helicteric acid and helicterilic acid, are characteristic components of Helicteres and are relatively rare amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Among these, UGT74M1 has been identified to be involved in the biosynthesis of triterpenes in Saponaria vaccaria [ 32 ]. HaCYPi3, CYP716, and TwCYP712K1 of the P450 family may be involved in triterpene metabolism and thus participate in the triterpene synthesis pathway, in which TwCYP712K1 has been shown to act on celastrol [ [33] , [34] , [35] ]. Transcriptome data showed that ten P450 genes and two GT genes were upregulated after co-culture.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, UGT74M1 has been identified to be involved in the biosynthesis of triterpenes in Saponaria vaccaria [ 32 ]. HaCYPi3, CYP716, and TwCYP712K1 of the P450 family may be involved in triterpene metabolism and thus participate in the triterpene synthesis pathway, in which TwCYP712K1 has been shown to act on celastrol [ [33] , [34] , [35] ]. Transcriptome data showed that ten P450 genes and two GT genes were upregulated after co-culture.…”
Section: Discussionmentioning
confidence: 99%